Effects of Ga, Nb, V, Zr, and Cr on the crystal structures and thermal behavior of CuAlMn shape memory alloys - Ozkul, Iskender; Karaduman, Oktay; Canbay, Canan Aksu (Sage Publications Ltd, 2024)
CuAlMn alloys are cheaper and more promising alloy types compared to NiTi alloys. In this study, based on CuAlMn shape memory alloy, thermodynamic and structural characteristics of some new alloys containing four elements were investigated in detail. In this study, five new quaternary shape memory alloys, each containing a CuAlMn base alloy and a different fourth additive element (Ga, Nb, V, Zr, and Cr), were produced. The properties of the obtained alloys were characterized using a series of analysis methods such as X-ray diffraction (XRD), optical microscopy, differential scanning calorimetry (DSC), and differential thermal analysis (DTA). The results showed the effects of different elements on the crystal structures of the alloys and how different elements could change the thermal behavior of the alloys.
Keywords: SMA; martensitic transformation; DTA; quaternary alloying elements; XRD